Resource Mobilization Strategies for Strengthening Da'wah Programs in Islamic Educational Institutions: Evidence from Southern Thailand - Seehabudin Samoh; Abdul Ghofur; Muhammad Sulthon (Journal of Counseling, Education and Society, 2025)
This study aims to analyze the resource mobilization strategies employed to strengthen da’wah programs in Islamic educational institutions, focusing on Ma’had Al-Bi’athat Ad-Diniyah Yala in Southern Thailand. Utilizing a case study methodology, the research examines how the institution navigates funding challenges through a hybrid model that integrates community-based social capital with emerging digital fundraising modalities. The findings reveal a complex dynamic where traditional religious and social values are reproduced within the Muslim minority community, while simultaneously negotiating symbolic legitimacy via digital transparency and accountability. This dual approach highlights a paradoxical tension between maintaining historic trust-based networks and meeting modern philanthropic demands. By applying Bourdieu’s theory of cultural capital and habitus, the study advances theoretical understanding of how hybrid fundraising strategies enable institutional adaptation amid socio-economic constraints and shifting donor behaviors. The research contributes to broader discourses on institutional transformation, social reproduction, and the evolving role of digital engagement in sustaining religious education within marginalized minority contexts.